The Effect of Encapsulated Stone Column Geometric Variations on Bearing Capacity and Road Embankment Stability over Soft Soil (Case Study: Aruk –Sp. Take Road Section, West Kalimantan) - I Made Surya Wisnu Pangestu; Indrasurya B. Mochtar; Noor Endah (Interdisciplinary Social Studies, 2025)
Soft ground with low bearing capacity and high compressibility is the main cause of embankment damage on the Aruk–Sp. Take road section, West Kalimantan. This research aims to evaluate the effectiveness of Encapsulated Stone Columns (ESC) as an alternative ground improvement method to increase the bearing capacity and stability of the embankment. The analysis was conducted using secondary soil data (SPT) from the most critical location (BH.04). Column geometry variations were modeled with diameters (D) of 0.7 m, 0.8 m, and 0.9 m, as well as varying distances between columns (s), to obtain an optimal design configuration. Bearing capacity was analyzed using Terzaghi's method, while embankment stability was analyzed using the Geo5 program. The results show that the bearing capacity of the foundation is a more critical design criterion than global slope stability. The ESC model with a low area replacement ratio (As < 0.19) maintains slope stability (SF > 1.5) but fails to withstand the planned embankment load of 330 kPa. Increasing the As value—through diameter enlargement or reduced column spacing—significantly improves the safety factor. The recommended geometry configuration (As ? 0.19) is safe for both bearing capacity and embankment stability under collapse conditions.